Motivations and benefits of outward foreign direct investment from India to India Multinationals - Saharia, Vandita (2008)
The economic liberalization and deregulation of the Indian economy through a series of bold economic reforms in 1991 has brought about a significant transformation in the economic and industrial landscape. Since these reforms which include liberalization of the Foreign Direct Investment (FDI) regime and integration of the countryÃÂ¢ÃÂÃÂs economy with the global economy, there has been a surge in the outflow of investments and more specifically Outward Foreign Direct Investment from India. This was initially through Greenfield investments with the latest trend being investments through Mergers and Acquisitions. Predominantly, the manufacturing sector has capitalized on these investments followed by services. Although OFDI from India began in the early part of the century, it was a trickle and is now in a ÃÂ¢ÃÂÃÂTake Off PhaseÃÂ¢ÃÂÃÂ and hence, it is essential to understand the reasons and motivations of Indian companies to engage in Outward Foreign Direct Investment. This study aims at understanding these reasons and motivations through a survey of Indian Multinationals. This study also aims at analyzing the benefits of Outward Foreign Direct Investment to the Indian multinational companies, outlining the measures to be taken to improve the laws prevalent in India to facilitate such investments and thereby contributing to the academic field and theories of Foreign Direct Investment. During the course of my research, I realized that this topic has not been delved into by many authors. Since research on this topic was few, my research also aims at providing a comprehensive and detailed understanding of the topic. Detailed analysis conducted on the topic shows that there are various firm-specific objectives driving Indian companies to invest abroad, some of them being, financial benefits, scale economies, access to markets, technology, global supply chains etc. It was also realized that the nature of these investments being long-term, firms take a few years before actually realizing full benefits from the investments.